A Review on Importance of Artocarpus heterophyllus L. (Jackfruit) - Ahasan Ullah Khan; Israt Jahan Ema; Md. Ruman Faruk; Shofiul Azam Tarapder; Anayat Ullah Khan; Sana Noreen; Muhammad Adnan (Journal of Multidisciplinary Applied Natural Science, 2021)
The Jackfruit (Artocarpus heterophyllus L.) is well-known as “poor man’s food” fruit in Bangladesh. It is widely consumed by most of the rural people, and it is the national fruit of Bangladesh. The main aim of this review is to document the medicinal significance of jackfruit, major parts and uses of the jackfruit in Bangladesh. This article was based on mostly a literature review. All parts of the fruit and plant are used as human food, animal feed, and wood source for furniture. Although jackfruit is the main fruit of the tree, it is used as furniture for its beautiful texture and wood color. Jackfruit contains anti-bacterial, anti-diabetic, anti-oxidant, anti-inflammatory, and anti-helminthic properties. The fruit is rich in carbohydrates, minerals, carboxylic acids, dietary fiber, vitamins, and minerals. The seed is rich in manganese, magnesium, potassium, calcium, iron, and lectins and thus meets up nutritional requirements for the rural people. The present study attempted to review the medicinal importance, health-promoting effects of jackfruit and seeds with special emphasis on their applications in the food.